Chronic fungal pyelonephritis with perurethral fungal ball: A rare case report - Teeli, Mehraj Ul Islam; Farooq, Amir; Maqsood, Muzafar; Salam, Imran; Nisaa, Qadar un; Manzoor, Seerat (Indian Journal of Case Reports, 2025)
Chronic fungal pyelonephritis, an uncommon and severe infection mostly affecting immunocompromised persons such as those with poorly controlled diabetes, offers substantial diagnostic and therapeutic hurdles, particularly when exacerbated by obstructive fungal forms. We report the case of a 45-year-old male with a history of hypertension and type 2 diabetes who arrived with fever, dysuria, and abdominal pain. Initial studies indicated a Candida albicans urinary tract infection with obstructive fungal balls. While oral fluconazole offered temporary relief, repeated problems necessitated percutaneous nephrostomy with Amphotericin B irrigation, with systemic antifungals, guided by imaging and susceptibility testing. This case underscores the diagnostic and therapeutic complexity of persistent fungal pyelonephritis in immunocompromised patients, underlining the crucial relevance of early diagnosis, targeted antifungal treatments, and prolonged follow-up to optimize results and prevent severe consequences.